PENGEMBANGAN VIDEO ANIMASI PEMBELAJARAN IPAS PADA MATERI WUJUD ZAT UNTUK SISWA KELAS IV SD - Neng Nitalia; Ali Ismail; Regina Lichteria Panjaitan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning media in the form of animated videos for the subject of Natural Science and Social Science (IPAS) on the topic of states of matter for fourth-grade elementary school students. The background of this research is based on the low interest in learning among students due to the limitations of the learning media used by teachers, resulting in a monotonous learning process. Therefore, there is a need for technology-based learning media that can attract students' interest and make the learning process more interactive. The research was conducted at a school in Sumedang Regency using the Research and Development (R&D) method and the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The data collection and processing were carried out through student response questionnaires and validation results from media and material experts. The validation results from media experts showed a